Self-care Agency and Its Influential Factors in Hemodialysis Patients - M Soodmand; G Ghasemzadeh; S Mirzaee; M Mohammadi; N Amoozadeh Lichaei; A Monfared (Iran University of Medical Sciences, 2019)
Background & Aims: Hemodialysis is currently a common treatment for chronic renal disease, which is associated with numerous limitations in the physical, mental and even social function of the patients. As such, self-care activities could significantly help hemodialysis patients to adapt to the course of their disease. The present study aimed to determine self-care agency and its influential factors in hemodialysis patients. Materials & Methods: This cross-sectional was conducted on the patients referring to Razi Educational-Therapeutic Hemodialysis Center in Rasht, Iran in 2017. In total, 126 patients were selected via random sampling. Data were collected using a two-section questionnaire of sociodemographic characteristics and modulated Chinese version of 28-statement self-care agency. Data analysis was performed using descriptive statistics (mean, standard deviation, frequency, and percentage) and analytical tests (independent t-test, correlation-coefficient, analysis of variance, and logistic regression analysis).  Results: Approximately 71.4% of the patients had optimal self-care abilities, and a significant correlation was observed between age and self-care agency (P=0.013). Moreover, education level was significantly correlated with self-care agency (P<0.0001). The logistic regression analysis also indicated that the increased age of the patients from the mean age was associated with the reduction of their self-care agency by 1.5 times. Conclusion: Although the majority of the patients had optimal self-care abilities, the results also indicated that with increased age and due to the treatment procedure and disease complications, hemodialysis patients were faced with limitations in proper self-care. Therefore, it is recommended that proper measures be taken regarding the care program of these patients, so that they could fully contribute to their care process as a member of the healthcare team.